Oxy-fuel co-gasification of coal and biomass for negative CO2 emissions. (15th December 2021) - Spiegl, Nicolas; Long, Xiangyi; Berrueco, Cesar; Paterson, Nigel; Millan, Marcos
Highlights: Oxy-fuel gasification of coals and mixtures with biomass have been studied. Lignite is a suitable fuel for oxy-fuel gasification in fluidised bed. Co-gasification of biomass with lignite improved the overall process performance. Processing biomass with lignite with CCS, net negative emissions can be achieved. Abstract: A novel process has been investigated to enable CO2 to be isolated as a concentrated stream from the exhaust of a power station, without the use of separate, downstream capture technology. In this concept, a fluidised bed gasifier is operated with pure O2 and CO2, recycled from the combusted fuel gas stream, combining the advantages of gasification, fluidised bed operation and use of oxygen. With the combination of CO2 capture and biomass as the feedstock, net negative emissions can be achieved. This is the fifth in a series of papers which investigate the underlying science of the concept. It studies the influence of the use of different coals and mixtures containing coal/biomass on the process performance. A continuously fed, laboratory scale spouted bed reactor has been used for this study, and Daw Mill coal (DM), German lignite (GL), Polish coal (PC) and Olive bagasse (OB) were used as fuels. Carbon conversions for DM and PC were around 20–30% and dominated by release by pyrolysis. High conversions (60–80%) were observed for GL and the char showed an appreciable gasification reactivity. Co-processing of OB with GL proved to be a good way to further improve the overall process performance and complete conversion was achieved under some conditions. Processing biomass with lignite, with CO2 capture, is a technically viable way of producing energy from a waste material with a negative process carbon footprint.